2009
DOI: 10.1104/pp.109.137042
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Biosynthetic Potential for Carotenoid Accumulation in Genetically Diverse Germplasm of Maize      

Abstract: Enhancement of the carotenoid biosynthetic pathway in food crops benefits human health and adds commercial value of natural food colorants. However, predictable metabolic engineering or breeding is limited by the incomplete understanding of endogenous pathway regulation, including rate-controlling steps and timing of expression in carotenogenic tissues. The grass family (Poaceae) contains major crop staples, including maize (Zea mays), wheat (Triticum aestivum), rice (Oryza sativa), sorghum (Sorghum bicolor), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
137
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 43 publications
7
137
1
1
Order By: Relevance
“…In particular transcript profiling led to discovery of the Hydroxylase3 locus that coincidently mapped to a carotene QTL, thereby prompting investigation of allelic variation in a broader collection. Vallabhaneni & Wurtzel (2009) …”
Section: Carotenoid Biosynthesis and Genetic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular transcript profiling led to discovery of the Hydroxylase3 locus that coincidently mapped to a carotene QTL, thereby prompting investigation of allelic variation in a broader collection. Vallabhaneni & Wurtzel (2009) …”
Section: Carotenoid Biosynthesis and Genetic Controlmentioning
confidence: 99%
“…Genetic variation at crtRB1 also affects hydroxylation efficiency among encoded allozymes, as observed by resultant carotenoid profiles in recombinant expression assays. Similarly, studies on natural maize genetic diversity carried out by Vallabhaneni et al (2009), have provided the identification of hydroxylation genes associated with reduced endosperm provitamin A content. In particular transcript profiling led to discovery of the Hydroxylase3 locus that coincidently mapped to a carotene QTL, thereby prompting investigation of allelic variation in a broader collection.…”
Section: Carotenoid Biosynthesis and Genetic Controlmentioning
confidence: 99%
“…Maize is considered a source of carotenoids, substances that are important for human health, given the capability as antioxidant and the activity as vitamin A precursor of some of these compounds (Rodriguez-Amaya, 2001;Vallabhaneni & Wurtzel, 2009). The variability in the concentration of carotenoids in grains have been observed in maize cultivars and inbred lines, making the increase of concentration these compounds in the edible part of the plant possible by genetic improvement, especially of those of biological significance, provitamin A carotenoids (pVAC), precursors of vitamin A (Janick-Buckner et al, 1999;Kurilich & Juvik, 1999;Cardoso et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These traits include, for example, the sum of related metabolites or the ratio of two related metabolites, such as precursors or products (Sauer et al, 1999;Weckwerth et al, 2004;Wentzell et al, 2007). With both linkage analysis and GWAS, derived traits that represent ratios based on metabolic pathways or known interactions have generated more significant associations compared with associations from absolute levels of metabolites (Wentzell et al, 2007;Vallabhaneni and Wurtzel, 2009;Wurtzel et al, 2012;Angelovici et al, 2013; GonzalezJorge et al, 2013;Lipka et al, 2013;Owens et al, 2014). One explanation for this phenomenon could be the higher heritability of metabolic ratios compared with content traits (Wentzell et al, 2007).…”
mentioning
confidence: 99%
“…In addition, Gu et al (2010) found that knocking out mitochondrial isovaleryl-CoA dehydrogenase, an enzyme in the Leu degradation pathway, results in a significant increase in 12 FAAs in a seed-specific manner (Gu et al, 2010). Taken together, these findings suggest that the inherent coordination of seed FAAs could be used as a tool to further unravel the genetic basis of quantitative traits, such as amino acids.Forward genetic approaches, such as linkage analysis, have proven to be powerful for identifying quantitative trait loci (QTLs) that control phenotypic variation for phenological and metabolic traits, such as flowering time and levels of carotenoids, tocochromanols, and amino acids in seed (Kowalski et al, 1994; Alonso-Blanco et al, 1998;Yan et al, 2000;Wong et al, 2004;Wentzell et al, 2007;Chander et al, 2008; Balasubramanian et al, 2009;Vallabhaneni and Wurtzel, 2009;Gutiérrez-Rojas et al, 2010;Maloney et al, 2010;Kochevenko and Fernie, 2011). Nevertheless, traditional linkage analysis to identify QTLs in biparental recombinant inbred line (RIL) populations has two major weaknesses: it captures narrow levels of allelic diversity as a result of only two parental lines, and it provides low mapping resolution due to the overall limited number of recombination events that occur while constructing the RIL population (Yu and Buckler, 2006;Korte and Farlow, 2013).…”
mentioning
confidence: 99%